Development of e-Learning Microsoft Sway as Innovation of Local Culture-Based Learning Media (Dinamika Pendidikan, 2017)
The research aims to know the produce e-learning Microsoft sway based on the local culture and the effectiveness of the implementation of media in accounting and economics learning at Universitas PGRI Madiun. This research was conducted in Accounting Education Study Program and Economic Education Study Program of Universitas PGRI Madiun, uses research and development method. It was started by preliminary study, then continued with media development stage. The media developed was tested in the two study programs. The trial test result was analyzed, then based on the analysis result, the media and instrument were improved. Media that has been improved to be final media then re-implemented in learning in the two study programs. The results of research show that the development of e-learning microsoft sway based on local culture and the effectiveness of media implementation in economic and accounting learning at Universitas PGRI Madiun run smoothly and effectively, and give positive impact on learning process.